A Policy Note on the Grant-in-Aid System in Indian Education : Main Issues and Options for Reform - World Bank (Washington, DC, 2014)
This policy note is aimed at contributing to a broader discussion on how the private sector can be best used to achieve priority educational goals in India. This paper includes the following contents: background and objectives; the grant-in-aid system in India - an historical perspective; size of the private aided sector in India - school education; size of the private aided sector in India - higher education; public expenditures on grants-in-aid; performance and costs of aided institutions; issues for reform in the GIA sector; recent attempts at reform; and recommendations.